The influence of gender on the perception of justice in the distribution of sports facilities - Mochamad Azhar Ilmi; Himawan Wismanadi; Noortje Anita Kumaat; Joesoef Roepajadi; Moh. Turi (Universitas Sriwijaya, 2024)
This study aims to investigate the influence of gender on the perception of fairness in the distribution of sports facilities in universities. The type of research used is quantitative research with a cross-sectional design. The population in this study is all active students at the State University of Surabaya, with a sample of 245 students aged 18-22 years, consisting of 122 male students and 123 female students. The research instrument used was a questionnaire consisting of three variables: perception of fairness, satisfaction with facilities, and interest in participation in sports. The data analysis techniques used include descriptive analysis and ordinal regression to test the hypothesis. The results showed that respondents' average perception of fairness was 3.68 with a standard deviation of 0.65. Regression analysis revealed that gender significantly influenced the perception of justice (β = 0.42, p < 0.01) and 0.19 or 19% of the perception of justice was explained by gender, where male students showed a more positive perception than female students. This study concludes that there is a significant difference in the perception of justice based on gender, which shows the need for more inclusive policies in distributing sports facilities in universities.